COGNITIVE PSYCHOTHERAPY INTEGRATION OF ABU ZAYD AL-BALKHI AND AARON BECK: A Comparative Study in Modern Psychotherapy: INTEGRASI PSIKOTERAPI KOGNITIF ABU ZAYD AL-BALKHI DAN AARON BECK: Studi Komparatif dalam Psikoterapi Modern - Purwadi Putra Sawaludin, Vicky; Nursidik; Basuki Roswanto (Jurnal Studi Islam dan Sosial, 2026)
Modern psychotherapy, particularly Cognitive Behavioral Therapy (CBT), has proven effective in clinical practice but remains limited in integrating spiritual dimensions, creating the need for a more holistic approach relevant to Muslim societies. This study aims to conduct a comparative analysis of Abu Zayd al-Balkhi’s cognitive psychotherapy concepts and Aaron Beck’s CBT, and to explore the potential integration of both within modern psychotherapy. The research employs a qualitative comparative literature study, examining Al-Balkhi’s classical works and Beck’s foundational CBT literature. The study finds that both emphasize the role of cognition in shaping emotions and behavior, yet differ in orientation: Beck focuses on clinical effectiveness, while Al-Balkhi highlights the balance of soul and body and closeness to God. These differences open the possibility of integration, resulting in the model of Islamic Cognitive Behavioral Therapy (ICBT) as the key finding of this research—an evidence-based therapy that is also spiritually meaningful. The contribution of this study is twofold: theoretically, it enriches Islamic psychology by integrating it with CBT; and practically, it offers an applicable model for Muslim communities to address the complexities of contemporary mental health.